2010
DOI: 10.1364/oe.18.001462
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of light output power of InGaN/GaN light-emitting diode by lateral epitaxial overgrowth using pyramidal-shaped SiO_2

Abstract: We report on the improvement of light output power of InGaN/GaN blue light-emitting diodes (LEDs) by lateral epitaxial overgrowth (LEO) of GaN using a pyramidal-shaped SiO(2) mask. The light output power was increased by 80% at 20 mA of injection current compared with that of conventional LEDs without LEO structures. This improvement is attributed to an increased internal quantum efficiency by a significant reduction in threading dislocation and by an enhancement of light extraction efficiency by pyramidal-sha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 24 publications
0
16
0
Order By: Relevance
“…Table 1 shows the absorption coefficients of the different media applied in this study. 3,8 To run the simulation, the light source and receiver must be set up after the structure is designed. As the light source, the active MQW layer is set up as the cubic light source.…”
Section: Simulationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Table 1 shows the absorption coefficients of the different media applied in this study. 3,8 To run the simulation, the light source and receiver must be set up after the structure is designed. As the light source, the active MQW layer is set up as the cubic light source.…”
Section: Simulationsmentioning
confidence: 99%
“…The patterned sapphire substrate (PSS) method has been reported to not only improve light extraction efficiency but also increase the internal light efficiency through a low dislocation effect when growing an epitaxial layer growth on the top of the sapphire substrate. [3][4][5][6] However, these studies are mostly based on lab experiments that are used to show if the efficiency is increased compared to the existing LEDs, which means the quantitative results are somewhat lacking. In order to quantitatively analyze the efficiency improvement from a PSS design, an LED has to pass through many processes.…”
Section: Introductionmentioning
confidence: 99%
“…For the state-of-the-art bulk templates (those grown with the traditional nucleation layer approach, i.e., epi-growth directly on sapphire), e.g., in commercial LEDs, defect densities still remain in the range of 10 8 cm −2 . The typical levels are, however, estimated to be in the 10 9 cm −2 range [3][4][5]. Further reduction of the defect densities requires special techniques for the relaxation of strain and/or termination of defects formed during the growth [6].…”
Section: Introductionmentioning
confidence: 99%
“…Many researchers have proposed various ways of overcoming the above-mentioned serious optical and structural drawbacks of nonpolar GaN. For instance, it has been reported that improved light-extraction efficiency can be achieved via texturing of a-plane GaN surfaces by photoenhanced chemical wet-etching [8], and employing the technique of lateral epitaxial overgrowth (LEO) using SiO 2 [9], instead of patterned sapphire substrate (PSS). Furthermore, it has been demonstrated by some research groups that reductions in threading dislocations (TDs) and stacking faults densities in a-plane GaN can be achieved by using the LEO technique [10].…”
Section: Introductionmentioning
confidence: 99%